(untitled) (World Bulletin of Education and Learning, 2025)
This article examines the central thematic conflict between good and evil in William Golding’s novel “Lord of the Flies”, emphasizing the author’s exploration of human nature when removed from the constraints of civilization. The study analyzes how moral values deteriorate as the boys on the island confront fear, power struggles, and survival instincts. Golding portrays good and evil not as external forces but as inherent dualities existing within each individual. By focusing on key characters such as Ralph, Piggy, Jack, and Simon, the article investigates the psychological and symbolic dimensions of their actions, revealing how societal order gradually collapses and innate savagery emerges. Special attention is given to the symbolic functions of major elements, including the conch, the “beast”, and the Lord of the Flies, as representations of morality, irrational fear, and primal violence. Through a close reading of the text and relevant critical perspectives, the research demonstrates that Golding challenges the notion of innocence in childhood by illustrating the fragile boundary separating civilization from barbarism. Ultimately, this article argues that “Lord of the Flies” offers a profound commentary on the perpetual struggle between good and evil that resides at the core of human existence.